WITHDRAWN: Determinants of Thai AEC engineer readiness - Duangporn Kraisuth; Vinai Panjakajornsak (My University, 2017)
This article has been withdrawn at the request of the author(s) and/or editor. The Publisher apologizes for any inconvenience this may cause. The full Elsevier Policy on Article Withdrawal can be found at https://www.elsevier.com/about/our-business/policies/article-withdrawal.
Keywords: Higher Education Learning Practices